Modelling anglers' fish release choices using logbook data - Gianluca Grilli; John A. Curtis; Stephen Hynes (The Economic and Social Research Institute (ESRI), 2019)
In this paper we model recreational anglers' decisions to voluntarily release their catch to improve fish stock conservation. Using a random utility framework, we compare anglers' utility of retaining and consuming fish versus increased stock conservation achieved by fish releases. The analysis is based on a dataset of fish landings from anglers fishing for salmon and sea trout in Ireland during the seasons 2010-2016. Results indicate that there is a statistically significant inverse association between the weight of a fish and the probability of release, with larger fish more likely to be retained for consumption. On average, anglers were willing to sacrifice around 2.5 kg of fish to improve conservation of salmon and sea trout stocks, with a median value of 1.48. Results also indicate that the release probability varies based on fishing methods, with the use of spinners, flyfishing and shrimps as bait to be more likely to be used for catch and release and live bait (i.e. worms) to retain the fish. Licence types and anglers' nationality are also important variables explaining release probability.
Keywords: 330